The arm-repeat protein NPRAP (Neurojungin) is a constituent of the plaques of the outer limiting zone in the retina, defining a novel type of adhering junction - Paffenholz, Rainer; Franke, Werner (Experimental cell research, 2002)
In the retina, special plaque-bearing adhering junctions are aligned to form a planar system (the “outer limiting zone,” OLZ) of heterotypic connections between the photoreceptor cells and the surrounding glial cells (“Müller cells”), together with homotypic junctions. In the plaques of these junctions, which contain N-cadherin—and possibly also related cadherins—we have identified, by immunolocalization techniques, a recently discovered neural tissue-specific protein, neurojungin, a member of the plakoglobin/armadillo protein family. In these plaques we have also detected other adherens plaque proteins, such as α- and β-catenin, protein p120, and vinculin, as well as proteins known as constituents of tight junction plaques, such as symplekin and protein ZO-1, and the desmosomal plaque protein plakophilin 2. This unusual combination of proteins and the demonstrated absence of plakoglobin define the OLZ junctions as a new and distinct category of adhering junction, which probably has special architectural functions.